Monetisasi dalam Strategi Komunikasi Lintas Budaya Bayu Skak Melalui Video Blog Youtube - Bernard Realino Danu Kristianto; Rustono Farady Marta (LUGAS Jurnal Komunikasi, 2019)
This study aims to understand the convergence of digital media into the reality of peak phenomenon of modern society needs in the present. The popular culture of exploiting new media as a means of monetization obscures the movitation and the purpose of new media itself is created.In the discussion, it will show how the owner of YouTube account Bayu Skak, doing self presentation as a representation of Java community in audio visual works, as well as how monetization runs on the video blogs he created in the media platform YouTube.The researchers concluded that the YouTube Media as one of the popular new media forms clearly offers space for modern society to make money and contribute to capitalism by providing an opportunity for account owners to present himself and work through audio-visual media.